Teachers’ Strategies for Fostering Social Character in Early Childhood within the School Environment - Zadela Putri Amalia; Rahmah Novianti (Universitas Sebelas Maret, 2026)
This study aims to analyze the strategies employed by teachers to cultivate social character among young children Social character development in early childhood serves as a critical foundation for fostering positive social interactions within educational environments. Utilizing a descriptive qualitative approach, this research involved five experienced teachers as the primary informants. Data were gathered through participatory observation, semi-structured interviews, and intensive documentation over a two-month. Data analysis was conducted using the Miles & Huberman model, encompassing data reduction, display, and verification through triangulation. The findings indicate that the primary strategies—comprising modeling, cooperative play, positive reinforcement, and effective communication—significantly enhance children's cooperation and empathy. However, the implementation of these strategies often faces challenges stemming from the heterogeneity of the children's backgrounds and a lack of synergy with parental involvement. Consequently, this study recommends strengthening school-family collaboration and implementing differentiated pedagogical training for teachers to optimize the development of adaptive social character in diverse early childhood settings.